Między przystępnością a nakłanianiem. Wykorzystanie efektu H2H w badaniach komunikacji marek - GRAŻUL-LUFT, AGNIESZKA; PIEKOT, TOMASZ (Stylistyka, 2025)
This article investigates whether and to what extent the H2H proximisation strategy, commonly used to assess language readability, can also be applied to analyse the persuasive and manipulative functions (conation) of brand communication. The H2H effect refers to the explicit marking of personal deixis in the text, such as sender and receiver references. Analysing these markers could facilitate the identification of distinct interpersonal communication styles. The analysed texts were polish texts from the websites and Facebook pages of the ten brands ranked as the most user-friendly globally (according to the Siegel+Gale Global Simplicity Index). Our mixed-methods approach combined automated analysis of the H2H effect with a qualitative examination of sentences containing explicit sender and receiver markers. The language of the analysed brands meets readability standards related to interpersonal communication. Most brands use a symmetrical H2H style, maintaining a similar balance of sender and receiver markers. However, the qualitative analysis revealed numerous non-prototypical uses of personal deixis, particularly in thecase of sender markers. Recipient markers (such as “you”) tend to exhibit clearerpragmatic roles, while sender markers (“I”, “we”) are more often used in complex, non-standard contexts. Most brands adopt a balanced, symmetrical relational style. The application of the H2H strategy depends largely on text type and communicative function, especially when language is used for conative purposes. This use of language can complicate readers’ perception of interpersonal relationships in brand communication.